Binder‐Free Growth of Aluminum‐Based Metal–Organic Frameworks on Aluminum Substrate for Enhanced Water Adsorption Capacity. (22nd October 2021) - Yang, Tianyu; Ge, Lurong; Ge, Tianshu; Zhan, Guowu; Wang, Ruzhu
Abstract: Coating metal–organic frameworks (MOFs) on metal substrates is an important research orientation in the applications of MOFs. However, the existing binder‐based coating method needs repetitive operations and unavoidably plugs the pores of MOFs, resulting in a reduction of the adsorption capacity. Herein, a binder‐free method is proposed to construct the MOF‐on‐metal structure. The well‐intergrown polycrystalline Al‐MOF layer on aluminum substrate is prepared by in situ synthesizing Al‐based MOFs (MIL‐96 and MIL‐100) with aluminum ions from the dissolution of aluminum substrates. The morphology and chemical compositions of the MOF coating layer are systematically characterized, and a pH‐controlled strategy is proposed to regulate the relative proportion of the hybrid MOFs. Importantly, the MOF‐on‐metal structure displays ultrahigh water adsorption capacity of 192.5 g m −2, which is the highest of all reported desiccant‐coated metal structures, and superior cycling stability. Further, the performance of a desiccant heat pump system utilizing MOF‐on‐metal structure is predicted, demonstrating that the operation period is 80% longer than a system with a binder‐based silica gel coating, and the average dehumidification capacity can reach 8.36 g kg −1 dry air. In conclusion, the new method enables the formation of binder‐free, low‐cost, and high‐performance MOF coating and has a broad prospect in energy‐efficient adsorption‐based applications. Abstract : Metal–organic framework (MOF)‐on‐metal structure composed of Al‐MOF layer and metal substrate is constructed by in situ synthesizing Al‐based MOFs with aluminum ions from the dissolution of aluminum substrates. The binder‐free Al‐MOF layer has an ultrahigh water adsorption capacity of 192.5 g m −2 and superior cycling stability under rigorous conditions and thus has a broad prospect in energy‐efficient adsorption‐based applications.